Comentarios y análisis sobre el proceso constituyente en Chile - Zegarra Llanos, Irene Jetsabel (2022)
With the social outbreak in Chile in October 2019, a series of demonstrations and citizen mobilizations of different sectors of society began, which promoted various requests for social claims and demands. It is from this event that, on November 12 of that year, a presidential speech was issued, through which three major agreements were proposed to overcome the crisis that was being experienced, and one of those agreements was the agreement for a new constitution.This promise gave rise to the formation of the Constitutional Convention, the body which, after a long and arduous period of work, has recently presented a new draft constitutional text, which will be accepted or rejected by means of a plebiscite to be held in September of this year. In this context, the purpose of the interview is to analyze and evaluate the most decisive aspects of the constitutional process.